Mammalian Contribution to Transmission of Schistosoma japonicum Infection in West Lore, Poso, Central Sulawesi, Indonesia - Novericko Ginger Budiono; Fadjar Satrija; Yusuf Ridwan; Ekowati Handharyani; Sri Murtini; Opyn Mananta (Jurnal Ilmu Ternak dan Veteriner, 2022)
Studies on the role of domestic animals in the transmission of schistosomiasis japonica in the West Lore Sub-district, Poso District, are still limited despite its importance as zoonosis. This study used a cross-sectional design to determine schistosomiasis prevalence in domestic mammals and identify the relative contribution of each mammalian species’ schistosomiasis transmission in the West Lore Sub-District. Fecal samples were obtained from 209 animals (seven buffaloes, 70 dogs, 44 cattle, 86 pigs, and two horses). The Danish Bilharziasis Laboratory technique was used to detect both the occurrence of S. japonicum egg in feces and the intensity of schistosomiasis infection. The examination of 1852 human fecal samples using the Kato-Katz method was carried out by the Laboratory of Schistosomiasis Lengkeka. The measurement of environmental pollution with S. japonicum eggs and the relative contribution of each species in the transmission was performed. The highest prevalence of S. japonicum infection in animals was in horses (100%; 2/2), cattle (54.55%; 24/44), and pigs (51.16%; 44/86). The prevalence in buffaloes and dogs was 28.57% (2/7) and 32.86% (23/70). Cattle (69.74%) were the main contributors to S. japonicum eggs contamination in the environment, followed by pigs (21.95%) and buffaloes (4.71%). This study reported a high prevalence of schistosomiasis in animals (45.46%), while low human schistosomiasis prevalence (0.59%).